2005
DOI: 10.1074/jbc.m402645200
|View full text |Cite
|
Sign up to set email alerts
|

Specific Structural Features of Heparan Sulfate Proteoglycans Potentiate Neuregulin-1 Signaling

Abstract: Neuregulins are a family of growth and differentiation factors that act through activation of cell-surface erbB receptor tyrosine kinases and have essential functions both during development and on the growth of cancer cells. One alternatively spliced neuregulin-1 form has a distinct heparin-binding immunoglobulin-like domain that enables it to adhere to heparan sulfate proteoglycans at key locations during development and substantially potentiates its activity. We examined the structural specificity needed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 46 publications
1
42
0
Order By: Relevance
“…The NRGs share structural similarity with Vn because both types of growth factors have an Ig domain in addition to the EGF domain . The Ig domain in NRG is required for binding to heparin, and sulfate groups including 6-O-sulfate groups play a role in the interaction (Li and Loeb 2001;Pankonin et al 2005). The addition of a Drosophila EGF ligand to the collection of known ligands regulated by Sulf1 highlights the broad role HSPGs play in signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NRGs share structural similarity with Vn because both types of growth factors have an Ig domain in addition to the EGF domain . The Ig domain in NRG is required for binding to heparin, and sulfate groups including 6-O-sulfate groups play a role in the interaction (Li and Loeb 2001;Pankonin et al 2005). The addition of a Drosophila EGF ligand to the collection of known ligands regulated by Sulf1 highlights the broad role HSPGs play in signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Some vertebrate EGF ligands are known to bind HSPGs, including some neuregulins (NRGs) and heparin-binding EGF (Pankonin et al 2005;Mahtouk et al 2006;Iwamoto et al 2010). The NRGs share structural similarity with Vn because both types of growth factors have an Ig domain in addition to the EGF domain .…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 demonstrates a partial alignment of three proteins (TPV-15L, hNRG1, and EGF) indicating the regions of the highest homology. Heparin binding variants of NRG1 are known to exist, where the domain responsible for heparin binding resides on an Ig-like domain near the N terminus of the EGF-like domain (7,9,35,36). This type of heparin binding motif is clearly absent from the amino acid sequence of TPV-15L.…”
Section: Bioinformatic Analyses Of Tpv-15l Proteinmentioning
confidence: 99%
“…Evidence for this notion was derived from the chicken embryo development model, where agrin (an HSPG) and NRG1 form localized complexes that synergistically concentrate to the basal lamina of the NMJ, potentiating a signal that upregulates expression of acetylcholine receptor genes (7,8). Later studies have also suggested that NRGs target specific HSPGs, preferentially choosing N-sulfate over 2-O-and 6-O-sulfate groups (9).…”
mentioning
confidence: 99%
“…Inhibition of sulfation through the use of chlorate or selective blockade of N-sulfation with a siRNA directed against the enzyme that promotes Nsulfation resulted in decreased NRG-1-induced erbB receptor activation. This specificity provides a means by which tissues can localize and potentiate NRG-1 signaling through modifications in glycosaminoglycan composition (52).…”
Section: Heparan Sulfate Chains and Cell Signalingmentioning
confidence: 99%